Free NPs as units in Finnish - Helasvuo Marja-Liisa (John Benjamins, 2022)
This article focuses on free NPs, i.e. noun phrases that are grammatically not part of any clause but form units of their own. Using the methodology of discourse-functional and interactional linguistics, I analyze the morphosyntactic, prosodic and interactional features of free NPs in conversational Finnish. With its rich morphological marking, Finnish provides an interesting perspective on free NPs: Morphosyntactic features, together with semantics, are crucial in determining the status of an NP as a clausal constituent or a free NP. The prosodic analysis shows that the majority of free NPs show clear prosodic boundaries, signalled for example by speaker change, coherent intonation contour, pause or pitch reset. Free NPs serve various interactional functions, such as making assessments or disambiguating referents. These are functions which operate on something already established in the discourse. Free NPs , however can also initiate something new for example by making requests or introducing new topics.